Comparison of primary percutaneous coronary intervention in patients with ST‐elevation myocardial infarction during and prior to availability of an in‐house STEMI system: Early experience and intermediate outcomes of the HARRT program for achieving routine D2B times <60 minutes. Issue 2 (25th February 2015) - Nguyen, Bryant; Fennessy, Michelle; Leya, Ferdinand; Nowak, Wojciech; Ryan, Michael; Freeberg, Sheldon; Gill, Jasrai; Dieter, Robert S; Steen, Lowell; Lewis, Bruce; Cichon, Mark; Probst, Beatrice; et al.
Abstract : Background: Over the last decade, significant advances in ST‐elevation myocardial infarction (STEMI) workflow have resulted in most hospitals reporting door‐to‐balloon (D2B) times within the 90 min standard. Few programs have been enacted to systematically attempt to achieve routine D2B within 60 min. We sought to determine whether 24‐hr in‐house catheterization laboratory coverage via an In‐House Interventional Team Program (IHIT) could achieve D2B times below 60 min for STEMI and to compare the results to the standard primary percutaneous coronary intervention (PCI) approach. Methods: An IHIT program was established consisting of an attending interventional cardiologist, and a catheterization laboratory team present in‐hospital 24 hr/day. For all consecutive STEMI patients, we compared the standard primary PCI approach during the two years prior to the program (group A) to the initial 20 months of the IHIT program (group B), and repeated this analysis for only CMS‐reportable patients. The D2B process was analyzed by calculating workflow intervals. The primary endpoint was D2B process times, and secondary endpoints included in‐hospital and 6‐month cardiovascular outcomes and resource utilization. Results: An IHIT program for STEMI resulted in significant reductions across all treatment intervals with an overall 57% reduction in D2B time, and an absolute reduction in mean D2B time of 71 min. There were no differences pre‐ and post‐program implementation in regard to individual or composite components of in‐hospital cardiovascular outcomes; however at 6 months, there was a reduction in cardiovascular rehospitalization after program implementation (30 vs. 5%, P  < 0.01). The IHIT program resulted in a significant reduction in length‐of‐stay (LOS) (90 ± 102 vs. 197 ± 303 hr, P  = 0.02), and critical care time (54 ± 97 vs. 149 ± 299 hr, P  = 0.02). Conclusions: Availability of an in‐house 24‐hr STEMI team significantly decreased reperfusion time and led to improved clinical outcomes and a shorter LOS for PCI‐treated STEMI patients. © 2015 Wiley Periodicals, Inc.